BAALC overexpression retains its negative prognostic role across all cytogenetic risk groups in acute myeloid leukemia patients. Issue 10 (23rd July 2013) - Damiani, Daniela; Tiribelli, Mario; Franzoni, Alessandra; Michelutti, Angela; Fabbro, Dora; Cavallin, Margherita; Toffoletti, Eleonora; Simeone, Erica; Fanin, Renato; Damante, Giuseppe
<x xml:space="preserve">Abstract</x> Overexpression of brain and acute leukemia cytoplasmic (BAALC) gene confers poor prognosis in cytogenetically normal acute myeloid leukemia (AML) patients, while less defined is its role in AML with abnormal karyotype. We evaluated the effect of BAALC overexpression on outcome of 175 adult AML patients with different cytogenetic risks. Karyotype was favorable in 13, intermediate in 117 and unfavorable in 45 patients, respectively. Quantitative BAALC expression was determined by real‐time PCR, with cut off value set at 50th percentile. BAALC was overexpressed in 87/175 (50%) patients, without association with cytogenetic status. High BAALC was associated with unmutated NPM (P = 0.006) and CD34 positivity (P < 0.0001). Complete remission (CR) was attained in 111 patients (63%), and was maintained at 5 years in 52 ± 7%. BAALC overexpression had a negative impact on CR achievement (P = 0.04), while did not influence relapse probability. Median survival was 22 months with a 5‐years overall survival (OS) of 35%. Factors with a negative impact on OS were older age (P = 0.0001), unfavorable cytogenetic (P = 0.005), ABCG2 overexpression (P = 0.03) and high BAALC levels (P = 0.01). We observed a worse outcome in patients with high BAALC expression through all cytogenetic risk categories: 5‐years OS was 100% vs. 71% in patients with favorable cytogenetics (P = 0.05), 55% vs. 40% in cases with intermediate karyotype (P = 0.04) and 34% vs. 23% in unfavorable cytogenetic subgroup (P = 0.02). BAALC overexpression identified AML patients with poor prognosis in all cytogenetic groups. Though relatively rare, BAALC positivity in patients with favorable or unfavorable karyotype significantly worsened survival. Am. J. Hematol. 88:848–852, 2013. © 2013 Wiley Periodicals, Inc.